The Establishment of Village Regulations in the Context of Village Democratization - Neta, Yulia; Budiyono, Budiyono; Firmansyah, Ade Arif; Evendia, Malicia (Fiat Justisia: Jurnal Ilmu Hukum, 2024)
The enactment of Law Number 6 of 2014 concerning Villages introduces a distinct dimension to the democratization process within villages, emphasizing recognition and subsidiarity that portrays villages not merely as geographic entities but as integral parts of their socio-cultural communities. Currently, the formulation of village regulations as a manifestation of village autonomy remains a stagnant process. This article aims to critically examine the development of village regulations within the framework of village democratization, employing doctrinal research methods alongside statutory and conceptual approaches. Findings reveal that village regulations constitute a subset of statutory regulations, incorporating provisions from higher-level frameworks while embodying community participation grounded in village-specific authority and rights. The transformation prompted by Law Number 6 of 2014 enhances the scope for village democratization, influencing the formulation of regulations that must meet both substantive and procedural requirements, thus presenting villages with opportunities and challenges in realizing local democratization effectively.